LEGAL CERTAINTY IN ELECTRONIC MANUFACTURING OF MORTGAGE CERTIFICATES: KEPASTIAN HUKUM DALAM PEMBUATAN SERTIPIKAT HAK TANGGUNGAN SECARA ELEKTRONIK - Aisyah Juliviani I; Moh. Saleh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The debt guarantee that will be given by the prospective debtor will be associated with a right to guarantee according to the type of guarantee submitted. In Indonesia itself, it has just implemented services through electronic means, services by carrying out a new interaction mechanism between the government and the community and for the benefit of other people who are interested, involving the use of technology and information (especially the internet) aimed at improving quality. in community service. According to the author, the Electronic Mortgage Service does not yet have legal protection for creditors so that the author uses normative legal research methods so that the author can use the basic analysis of the laws and regulations or some other legal document. The author's purpose in this study aims to identify and analyze forms of legal protection for creditors in making Electronic Mortgage certificates.